Multifaceted Biological Properties of Verbascoside/Acteoside: Antimicrobial, Cytotoxic, Anti-Inflammatory, and Immunomodulatory Effects - Mirjana Marčetić; Biljana Bufan; Milica Drobac; Jelena Antić Stanković; Nevena Arsenović Ranin; Marina T. Milenković; Dragana D. Božić (Antibiotics)
Verbascoside is a polyphenolic compound that belongs to the phenylethanoid glucosides. It occurs in more than 220 plant species. The species with high content of this compound are used in folk medicine, and in modern phytotherapy, mostly based on its recognized anti-inflammatory and antimicrobial effects. Studies conducted so far confirmed these effects, and also pointed to others (i.e., anti-cancer, neuro-, cardio-, hepato-, and nephro-protective). This review presents data on the chemistry, occurrence, and biosynthesis of verbascoside. Additionally, it focuses on the cytotoxic, antimicrobial, anti-inflammatory, and immunomodulatory effects, as well as the main cellular and molecular mechanisms of its action.